Immunotherapy in association with stereotactic radiotherapy for non-small cell lung cancer brain metastases: results from a multicentric retrospective study on behalf of AIRO. Issue 10 (29th May 2021) - Scoccianti, Silvia; Olmetto, Emanuela; Pinzi, Valentina; Osti, Mattia Falchetto; Di Franco, Rossella; Caini, Saverio; Anselmo, Paola; Matteucci, Paolo; Franceschini, Davide; Mantovani, Cristina; Beltramo, Giancarlo; Pasqualetti, Francesco; et al.
Abstract: Background: To define efficacy and toxicity of Immunotherapy (IT) with stereotactic radiotherapy (SRT) including radiosurgery (RS) or hypofractionated SRT (HFSRT) for brain metastases (BM) from non-small cell lung cancer (NSCLC) in a multicentric retrospective study from AIRO (Italian Association of Radiotherapy and Clinical Oncology). Methods: NSCLC patients with BM receiving SRT + IT and treated in 19 Italian centers were analyzed and compared with a control group of patients treated with exclusive SRT. Results: One hundred patients treated with SRT + IT and 50 patients treated with SRT-alone were included. Patients receiving SRT + IT had a longer intracranial Local Progression-Free Survival (iLPFS) (propensity score-adjusted P = .007). Among patients who, at the diagnosis of BM, received IT and had also extracranial progression ( n = 24), IT administration after SRT was shown to be related to a better overall survival (OS) ( P = .037). A multivariate analysis, non-adenocarcinoma histology, KPS = 70 and use of HFSRT were associated with a significantly worse survival ( P = .019, P = .017 and P = .007 respectively). Time interval between SRT and IT ≤7 days ( n = 90) was shown to be related to a longer OS if compared to SRT-IT interval >7 days ( n = 10) (propensity score-adjusted P = .008). The combined treatment was well tolerated. No significant difference in terms of radionecrosis between SRT + IT patients and SRT-alone patients was observed. The time interval between SRT and IT had no impact on the toxicity rate. Conclusions: Combined SRT + IT was a safe approach, associated with a better iLPFS if compared to exclusive SRT.